2001
DOI: 10.1088/0253-6102/36/2/245
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Quantum Coherence in Antiferromagnetic Molecular Magnets

Abstract: The macroscopic quantum coherence in a biaxial antiferromagnetic molecular magnet in the presence of magnetic field acting parallel to its hard anisotropy axis is studied within the two-sublattice model. On the basis of instanton technique in the spin-coherent-state path-integral representation, both the rigorous Wentzel-Kramers-Brillouin exponent and preexponential factor for the groundstate tunnel splitting are obtained. We find that the quantum fluctuations around the classical paths can not only induce a n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…[150] Some extensions or alternative explications of Garg's result can be found in Refs. [151,152,153,154]. The period of oscillation is given by [128]:…”
Section: Semi-classical Descriptionsmentioning
confidence: 99%
“…[150] Some extensions or alternative explications of Garg's result can be found in Refs. [151,152,153,154]. The period of oscillation is given by [128]:…”
Section: Semi-classical Descriptionsmentioning
confidence: 99%
“…in a quantum ring (type-I quantum dot). This has spurred a considerable search and study of the optical AB effect of neutral excitons in semiconductor quantum rings by both theoretical [3][4][5][6][7][8][9] and experimental 1,12 groups.…”
Section: Introductionmentioning
confidence: 99%
“…With the advance of lithography and semiconductor growth techniques, the nanoring-like devices [5][6][7][8] have been realized experimentally. Due to unique character of the nanoring, the self-assembled quantum ring has become the best ideal candidate to observe Aharonov-Bohm (A-B) oscillation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, some researchers had paid their attention to A-B effect of neutral exciton in two-dimensional quantum ring. For instance, Hu et al [9] theoretically studied the magnetic field effects on exciton in an InAs nanoring, They found that the A-B effect of exciton only exists in a finite (but small) width nanoring in the presence of Coulomb correlation. Ribeiro et al [14] experimentally presented a magneto-photoluminescence study of type-II InP/GaAs self-assembled quantum dot, which revealed that A-B type oscillations for neutral excitons when angular momentum of hole ground state ranges from l h = 0 to l h = 1, 2, and 3.…”
Section: Introductionmentioning
confidence: 99%